Examining perceptions of food assistance on household food security and resilience in Malawi - Margolies, Amy; Kalagho, Kenan; Kazembe, Cynthia (International Food Policy Research Institute, 2018)
Improving social assistance programs is imperative to addressing problems of poverty and vulnerability in Malawi. Emergency aid has played an important role in alleviating hunger during humanitarian crises such as those in 2015-16 and 2016-17. However, the Government of Malawi and development partners recognize that emergency responses are not a sustainable solution to address vulnerability. This qualitative study examines the characteristics of resilient households and perceived effects of programs to improve food security and resilience from the perspectives of the beneficiaries and communities they serve. This beneficiary-centered approach explores socially-defined concepts of resilience, associated coping strategies, norms and political dynamics affecting programs. These findings can provide useful insights to improve the effectiveness of social assistance programs in this context.